FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS - Muhamad Ilkham; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
This study aimed to analyze the factors which affect the willingness to pay taxes. Variables used in this research is the willingness to pay taxes as a dependent variable, pay taxes awareness, knowledge and understanding of tax laws, the perception of the effectiveness of the tax system as independent variables.This study uses a quantitative method where the data obtained from the questionnaire with purposive random sampling method. Analysis of the data in this study using multiple linear regression with SPSS for Windows.The results of this study are as follows: (1) awareness of paying taxes positive and significant effect on the willingness to pay taxes, (2) knowledge and understanding of regulations, taxation positive and significant effect on the willingness to pay taxes, (3) the perception of the effectiveness of the tax system positive and significant effect on the willingness to pay taxes.